Psychometric Evaluation of Dietary Self-Efficacy and Outcome Expectation Scales in Female College Freshmen. (November 2014) - Kedem, Leia E.; Evans, Ellen M.; Chapman-Novakofski, Karen
Lifestyle interventions commonly measure psychosocial beliefs as precursors to positive behavior change, but often overlook questionnaire validation. This can affect measurement accuracy if the survey has been developed for a different population, as differing behavioral influences may affect instrument validity. The present study aimed to explore psychometric properties of self-efficacy and outcome expectation scales—originally developed for younger children—in a population of female college freshmen ( N = 268). Exploratory principal component analysis was used to investigate underlying data patterns and assess validity of previously published subscales. Composite scores for reliable subscales (Cronbach's α ≥ .70) were calculated to help characterize self-efficacy and outcome expectation beliefs in this population. The outcome expectation factor structure clearly comprised of positive (α = .81-.90) and negative outcomes (α = .63-.67). The self-efficacy factor structure included themes of motivation and effort (α = .75-.94), but items pertaining to hunger and availability cross-loaded often. Based on cross-loading patterns and low Cronbach's alpha values, respectively, self-efficacy items regarding barriers to healthy eating and negative outcome expectation items should be refined to improve reliability. Composite scores suggested that eating healthfully was associated with positive outcomes, but self-efficacy to do so was lower. Thus, dietary interventions for college students may be more successful by including skill-building activities to enhance self-efficacy and increase the likelihood of behavior change.